Transmission of Intergenerational Parenting Attitudes and Natural Mentorship: Associations Within the LONGSCAN population. (October 2020) - Kaferly, James; Furniss, Anna; Allison, Mandy A.
Abstract: Background: Evidence suggests that families transmit child maltreatment and parenting attitudes. Natural mentorship may mediate intergenerational parenting attitudes' risk for maltreatment but has not been studied. Objective: To compare parenting attitudes between adolescents exposed to or at risk for maltreatment and their caregivers and to determine if natural mentorship mediates differences in parenting attitudes' maltreatment risk. Participants and Setting: The study included 779 children and their caregivers from the Longitudinal Studies of Child Abuse and Neglect (LONGSCAN) study, Methods: Standardized measures assessed parenting attitudes, natural mentorship and demographic characteristics. Repeated measures, multivariable logistic regressions were used to predict low risk parenting attitudes for maltreatment among adolescents with and without natural mentors. Results: In adjusted analysis, natural mentorship did not predict an adolescent having low risk parenting attitudes when their caregivers had moderate or high risk attitudes: appropriate empathy adjusted odds ratio [aOR] = 1.26; 95% confidence interval [CI] 0.52 -3.01; appropriate expectations aOR = 1.35; CI 0.62-2.93; physical punishment rejection aOR = 1.74; CI 0.78-3.88; and appropriate roles aOR = 1.11; CI 0.57-2.18. Low risk caregiver parenting attitudes for appropriate empathy related to adolescents having low risk empathy attitudes (aOR = 2.89; CI 1.31-6.37). Male gender, African American race and Hispanic ethnicity were negatively associated with an adolescent having low risk parenting attitudes for maltreatment. Conclusions: Natural mentorship did not mediate adolescent parenting attitudes. While prevention and intervention strategies should include natural mentoring given positive health impacts, services must be cognizant of and designed for gender, racial and ethnic diversity.